Green space and preterm birth: A systematic review study - Nasim Sadat Pajohanfar; Mohammad Miri; Saiedeh Mehrabadi; Roghaieh Rahmani Bilandi (Mashhad University of Medical Sciences, 2020)
Introduction: The effect of environment on reproductive health and pregnancy outcomes has been expressed in some epidemiological studies. Exposure to green space has been shown to improve health as well as improve fetal growth and reduce the risk of pregnancy complications. This systematic review study was performed with aim to determine the relationship between green space and preterm birth. Methods: In this review study, to obtain relevant studies, we searched the English databases of Pubmed, Scopus, Web of science and Persian databases of Iran Medex, SID and Magiran published until 8 April 2020, with the English and Persian keywords of green space and preterm birth and all possible combinations. Results: From 6964 articles, 18 (12 cross-sectional studies and 6 cohort studies) which met the inclusion criteria were included in the study. Most studies evaluated green space using the normalized Index of Vegetation Difference (NDVI), proximity to green space, and distance to the park. The results of 9 studies showed no relationship between green space and preterm birth, and other studies reported conflicting results on protective effect of green space on preterm birth. Conclusion: The results of most studies showed no association between green space and preterm birth and gestational age at delivery time. While some studies reported conflicting results on protective effect of green space on preterm birth. Therefore, it is suggested that further studies be conducted in this area.